Pressure pain mapping of equine distal joints: feasibility and reliability - Gisler, Jana; Chiavaccini, Ludovica; Blum, Severin; Montavon, Stéphane; Spadavecchia, Claudia (Frontiers in Pain Research, 2024)
Background Osteoarthritis is a prevalent degenerative joint disease initiating chronic pain and lameness in horses. While several objective gait analysis systems have been developed and validated to quantify lameness severity in horses, methods to evaluate whether peripheral sensitization contributes to the pain experienced are missing. Objectives To evaluate whether periarticular pressure pain mapping could be proposed as an auxiliary assessment tool in horses. Specific aims were to evaluate the feasibility and intra- and inter-rater reliability of pressure pain thresholds (PPT) determination at sites overlying the distal thoracic limb joints of clinically healthy horses. Study design Prospective, randomized validation study. Methods For feasibility assessment, PPT were measured with a hand-held digital algometer at six periarticular landmarks (2 sites per joint, 3 joints) bilaterally on the distal thoracic limb of 40 healthy horses (20 warmblood and 20 Freiberger). The joints tested were the metacarpophalangeal, on the latero-palmar and dorsal aspects (L-MCP and D-MCP), the proximal interphalangeal, on the dorsal and palmar aspect (D-PIP and P-PIP) and the distal interphalangeal, on the dorsal and lateral aspect (D-DIP and L-DIP). A feasibility score, ranging from 0 to 5, was attributed to each testing session. For intra- and inter-rater reliability assessment, L-MCP and D-MCP were selected to be tested again at 2 weeks intervals in 20 out of the 40 horses. Data were analyzed using a mixed-effect linear model to test differences in threshold per site and limb. Intra- and inter-rater correlation was calculated. Bland-Altman plots were performed to evaluate the variability of the measures. Results The procedure was considered feasible (score <2) in 95% of horses (95% CI 88%–100%). Overall, median [interquartile range (IQR)] PPT was 9.4 (7.5–11.3) N. No significant side differences were found. P-PIP and D-DIP recorded significantly lower PPT (p < 0.001 and p = 0.002, respectively) than L-MCP. Median (IQR) were 9.9 (7.3–12.4) N, 8.4 (6.1–10.5) N and 9.0 (7.4–10.6) N for L-MCP, P-PIP and D-DIP, respectively. The intra-rater agreement was 0.68 (95% CI 0.35–0.86) for L-MCP, and 0.50 (95% CI 0.08–0.76) for D-MCP. Inter-rater agreement was 0.85 (95% CI 0.66–0.94) for L-MCP and 0.81 (0.57, 0.92) for D-MCP. Main limitations Evaluation of feasibility was performed only for distal thoracic limbs joints; no data are provided for hind limbs or proximal joints. Only warmblood and Freiberger horses were included. Intra- and inter-rater reliability assessments were performed exclusively on data collected at the MCP joint. Conclusion Pressure pain mapping of distal thoracic limb joints was feasible in horses. Local sensitivity differed among sites and no side differences were noticed. Data collected from the MCP joint suggest highly variable, subject dependent intra-rater reliability, ranging from poor to good, and good to excellent inter-rater reliability. Further studies evaluating pathologic vs. healthy joints are needed before recommendations can be made about clinical usability and diagnostic validity.